Concussion Education and Management for School Nurses - Mgonja, Brooke Wright (The University of Arizona., 2016)
Background: Despite the increased awareness and education to the public, concussions in children continue to ensue without proper concussion education and management in school systems. Whether the child suffers a concussion in school or at home, it is essential for school nurses to have proper concussion education and evidence based management strategies to further monitor post-concussive symptoms in the school setting. Concussion symptoms can affect the student up to 7-10 days following the injury. Concussions can range from mild to severe, with symptoms lasting hours, days, months or longer. Children who experience a concussion can experience academic challenges that will affect them in the classroom. Without proper concussion education for school nurses, concussed youth may experience post-concussive symptoms. School nurses have a significant role, collaborating with the parents, providers, and the student in providing accommodations and support while transitioning back into the classroom. Purpose: To assess the knowledge of Utah school nurses regarding concussion education and management of the concussed student. In addition evaluating the educational intervention, which changed the knowledge base of the participants. Methods: A one group pre-test and post-test design was used. Study materials were emailed via the Utah School Nurse Association listserv to all Utah school nurses. A concussion educational power point was provided to these nurses before having them complete the post-test. Results: The results of the paired sample t-test revealed that there was a significant difference (p= .000) in comparison of the pre-test and post-test results after viewing the concussion educational power point. Conclusion: The results of this study showed that there was a significant difference between pre-test and post-test results after viewing the concussion educational power point. Therefore it can be concluded that providing education and awareness regarding concussion and its management will increase the knowledge and ultimately may change practice which in turn may improve patient outcomes.